On the surface of the theory of music used in the peoples of the East arrival - S.SH.Raximov (Peerian Journals Publishing, 2022)
Music has accompanied man for centuries, reflecting his work, life, feelings and experiences, thoughts and dreams.
Keywords: music; Chertma instrument; Munojat; dutor